The Use of Mobile Applications and Wearable Devices in Physical Education: Implications for Performance Monitoring and Evaluation - Muh Ilham Aksir (Program Studi Pendidikan Jasmani Kesehatan dan Rekreasi, 2025)
The rapid development of mobile applications and wearable devices has transformed the landscape of physical education by enabling real-time monitoring, personalized feedback, and data-driven performance evaluation. This study employs a literature review approach to examine how digital technologies contribute to enhancing the effectiveness of teaching, learning, and performance assessment in physical education across various educational levels. Findings from international and national studies (2020–2025) indicate that the integration of mobile and wearable technologies significantly improves students’ motivation, engagement, and physical activity levels while allowing teachers to design adaptive and evidence-based instructional strategies. These tools provide accurate physiological and behavioral data—such as heart rate, activity duration, and intensity—that support both formative and summative assessments. However, challenges remain in ensuring data privacy, device accessibility, and teachers’ digital literacy. Overall, the implementation of mobile applications and wearable devices represents a pivotal shift toward a more modern, measurable, inclusive, and performance-oriented physical education system.